Caracterización del sistema de los factores de crecimiento similares a la insulina (IGFs) en el establecimiento del feocromocitoma y en la progresión de tumores de sistema nervioso central (SNC) en pacientes pediátricos - Martin, Ayelen (2019)
The aim of this Doctoral Thesis was to characterize the role of the IGFs system in tumour development, by means of two different paediatric tumours: Pheochromocytoma, associated to hereditary endocrine disease, and glioma, the most frequent solid tumour in children. Our in vitro and in vivo results suggest that IGF-1 through IGF-1R may be involved in early stages of pheochromocytoma establishment, contributing to tumour cells anchorage by interaction with both matrix and soluble factors produced by tumour microenvironment fibroblasts. In paediatric gliomas, IGF-1 expression was higher in high grade gliomas, and IGF-1R nuclear localization was significantly associated with both high grade tumours and increased risk of death. In vitro, IGF-1R overexpression and nuclear localization contributed to an aggressive phenotype of glioblastoma by increasing motility and metabolism of tumour cells, which resulted in earlier development of bigger tumours in vivo. With this work, we achieved our translational research goal by combining the efforts of both, clinicians devoted to children´s medical assistance and researchers, focused on basic studies.